2014
DOI: 10.1002/pi.4815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure–property relationships of novel thiazole‐containing poly(amide imide)s with high refractive indices and low birefringences

Abstract: Thiazole‐containing poly(amide imide)s with high thermal stability, excellent solubility, high refractive indices and low birefringences are successfully developed. The structure–property relationships of these polymers are also studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Thiazole ring as a substituent containing sulfur can contribute to the high refractive index of polymers. In our previous works, polymers containing thiazole with high refractive index, low birefringence, high thermal stability, and good solubility in common organic solvents were designed and synthesized [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Thiazole ring as a substituent containing sulfur can contribute to the high refractive index of polymers. In our previous works, polymers containing thiazole with high refractive index, low birefringence, high thermal stability, and good solubility in common organic solvents were designed and synthesized [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…7,31,32 We have reported that polyimides containing pyrimidine units exhibited high n values over 1.7. As for these polyimides, the lower transparency at the shorter visible wavelengths due to their aromatic imide-phenyl structure is, however, a critical problem for lens applications.…”
Section: Introductionmentioning
confidence: 98%
“…For most of the polymeric materials in our life, their conductivities are very low because a cluster of free electrons could not flow along their backbones. For example, poly(amide-imides) (PAIs) possessing good mechanical and thermal properties have been considered to be excellent engineering materials, but their application in the conductive field has been limited due to their poor conductivity [7,8,9,10,11]. The insulator–conductor transition could be achieved by incorporating conductive fillers into the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%